2011
DOI: 10.1152/japplphysiol.00930.2010
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic mechanisms do not contribute to age-related decreases in calf venous compliance

Abstract: Limb venous compliance decreases with advancing age, even in healthy humans. To test the hypothesis that adrenergic mechanisms contribute to age-associated reductions in limb venous compliance, we measured calf venous compliance before and during acute systemic α- and β-adrenergic blockade in eight young (27 ± 1 yr old, mean ± SE) and eight older healthy men (67 ± 2 yr old). Calf venous compliance was determined in supine subjects by inflating a thigh-collecting cuff to 60 mmHg for 8 min and then decreasing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 36 publications
0
19
1
Order By: Relevance
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (86)(87)(88)90,92,93). In accordance, we found that 10% of the subjects at 55 mmHg and almost 75% of the subjects at 60 mmHg displayed a negative Ccalf with the QRE.…”
Section: Venous Wall Modelmentioning
confidence: 51%
See 3 more Smart Citations
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (86)(87)(88)90,92,93). In accordance, we found that 10% of the subjects at 55 mmHg and almost 75% of the subjects at 60 mmHg displayed a negative Ccalf with the QRE.…”
Section: Venous Wall Modelmentioning
confidence: 51%
“…Other factors, such as physical activity and sympathetic tone, could influence the measurements of Ccalf (87,132). However, there were no differences in physical activity between the groups and although activation of the sympathetic system has been shown to lower unstressed venous volume, increased sympathetic activation does not appear to directly affect venous compliance (90,93).…”
Section: Effects Of Venous Compliance On Lbnp Tolerancementioning
confidence: 96%
See 2 more Smart Citations
“…Present assessments commonly use a mathematically derived quadratic regression equation (QRE) to model the venous pressure-volume curve and the first derivative of this equation to characterize venous compliance. With this approach, venous compliance is bound to become negative at a pressure within or very close to the applied physiological pressure range, precluding a valid interpretation (13,17,(32)(33)(34)43).Venous compliance has not been accurately measured in a well-defined VVS population, although lower limb venous pooling may be of pathophysiological importance. The aim of the present study was, therefore, 1) to introduce and validate a new physiologically derived three-parameter venous wall model (VWM) for the characterization of the venous pressure-volume relationship and 2) to accurately study calf venous compliance (C calf ), as well as the calf venous capacitance (V cap ) response (blood pooling), and assess its impact on orthostatic tolerance to lower body negative pressure (LBNP) in women diagnosed with VVS and matched controls.…”
mentioning
confidence: 99%